Meningkatkan Hasil Belajar Siswa Melalui Implementasi Model Pembelajaran Make A Match di SMP Negeri 2 Kayangan - Iswantari, Indah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
The purpose of this study was to improve student learning outcomes through the implementation of the Make a Match learning model in SMPN 2 Kayangan. The research method used was classroom action research with 29 students as subjects. The research instrument used was a learning achievement test. While the data analysis of the research useed descriptive qualitative and qualitative analysis techniques. The result of this study indicated that the application of the make a match learning model could improve the learning outcomes of science in class 9.1 students of SMPN 2 Kayangan in academic year 2017/2018. Student learning outcomes before the application of make a match learning were very low, in which the classical completeness score was only 20.7%. After taking action by applying the make a match learning model in cycle II, a classical completeness value was 86.2% obtained where 25 students who scored above the KKM. And, in the third cycle, the classical completeness value was 93.1% where 27 students got a score above the KKM.